Terpene derivatives as a potential agent against antimicrobial resistance (AMR) pathogens - Mahizan, Nik Nur Amirah; Yang, Shun Kai; Moo, Chew Li; Song, Adelene Ai Lian; Chong, Chou Min; Chong, Chun Wie; Abushelaibi, Aisha; Lim, Erin Swee Hua; Lai, Kok Song (MDPI, 2019)
The evolution of antimicrobial resistance (AMR) in pathogens has prompted extensive research to find alternative therapeutics. Plants rich with natural secondary metabolites are one of the go-to reservoirs for discovery of potential resources to alleviate this problem. Terpenes and their derivatives comprising of hydrocarbons, are usually found in essential oils (EOs). They have been reported to have potent antimicrobial activity, exhibiting bacteriostatic and bactericidal effects against tested pathogens. This brief review discusses the activity of terpenes and derivatives against pathogenic bacteria, describing the potential of the activity against AMR followed by the possible mechanism exerted by each terpene class. Finally, ongoing research and possible improvisation to the usage of terpenes and terpenoids in therapeutic practice against AMR are discussed.